A Commentary Against Aboriginal to non-Aboriginal Adoption - Richard, Kenn (First Peoples Child & Family Review, 2004)
This article focuses on the author’s experience and observations respecting the appropriateness of adopting Aboriginal children into non-Aboriginal settings, and its impact on children, youth and parents receiving services from an Aboriginal child and family services agency in Toronto.